A Concise Review of Ketogenic Dietary Interventions in the Management of Rare Diseases. (15th February 2021) - Hettiarachchi, D.; Lakmal, K.; Dissanayake, V. H. W.
Abstract : Dietary interventions are now being used as an adjunct therapy in the treatment of rare diseases. One such method is the high-fat, moderate-protein, and very low-carbohydrate diet which produces ketosis and therefore called the ketogenic diet. Some of the more common conditions that are treated with this method are pharmacoresistant epilepsy, infantile spasms, glycogen storage diseases, and other forms of rare metabolic disturbances. With this review, we look at different uses of the ketogenic diet in treating rare diseases and the recommendations based on current evidence.